Multi-objective optimal power flow considering the multi-terminal direct current - Ayachi , B.; Boukra , T.; Mezhoud , N. (Electrical Engineering & Electromechanics, 2021)
Introduction. In recent years, transmission systems comprise more direct current structures; their effects on alternating current power system may become significant and important. Also, multi-terminal direct current is favorable to the integration of large wind and solar power plants with a very beneficial ecological effect. The novelty of the proposed work consists in the effects of the aforementioned modern devices on transient stability, thus turn out to be an interesting research issue. In our view, they constitute a new challenge and an additional complexity for studying the dynamic behavior of modern electrical systems. Purpose. We sought a resolution to the problem of the transient stability constrained optimal power flow in the alternating current / direct current meshed networks. Convergence to security optimal power flow has been globally achieved. Methods. The solution of the problem was carried out in MATLAB environment, by an iterative combinatorial approach between optimized power flow computation and dynamic simulation. Results. A new transient stability constrained optimal power flow approach considering multi-terminal direct current systems can improve the transient stability after a contingency occurrence and operate the system economically within the system physical bounds. Practical value. The effectiveness and robustness of the proposed method is tested on the modified IEEE 14-bus test system with multi-objective optimization problem that reflect active power generation cost minimization and stability of the networks. It should be mentioned that active power losses are small in meshed networks relative to the standard network. The meshed networks led to a gain up to 46,214 % from the base case.